Whole new world a twisted tale - Braswell, Liz (Los Angeles Disney Press, 2016)
"Aladdin is a street rat. Like most, he's just trying to survive another day in impoverished Agrabah. Jasmine is a princess, one who is about to enter into an arranged marriage. All she wants is to escape her fate, to see what lies beyond the palace walls. But everything changes when the sultan's trusted advisor, Jafar, suddenly rises to power. With the help of an ancient lamp, Jafar attempts to break the laws of magic and gain control over love and death. Soon Aladdin and the deposed princess Jasmine must unite the people of Agrabah in rebellion to stop the power-mad ruler threatening to tear the kingdom apart."--Page 4 of cover.
Based on: Aladdin, the 1992 Disney film.
Includes excerpt from "Once upon a dream" by Liz Braswell.
Accelerated Reader AR
114414
Keywords: Aladdin -- (Legendary character) -- Fiction; Magic -- Juvenile fiction; Revolutions -- Juvenile fiction; Princesses -- Juvenile fiction; Young adult fiction; Teen fiction; Adaptations; Fantasy fiction; Fiction; Juvenile works; Young adult works; Fantasy fiction; Adaptations